NLP-enhanced inflation measurement using BERT and web scraping - Berki, Martin; Andicsova, Vanesa; Oravec, Milos (Frontiers in Artificial Intelligence, 2025)
In this research note, we explore the integration of natural language processing (NLP) and web scraping techniques to develop a custom price index for measuring inflation. Using the Harmonized Index of Consumer Prices (HICP) as a benchmark, we created a database of consumer electronics product data through web scraping. Using the BERT model for classification, we achieved a high-performance classification of approximately 10,000 items into COICOP categories, with an accuracy of 94.56 %, macro precision of 79.41 %, and weighted precision of 94.07 % on validation data. Our custom index, particularly with weighted and median methodologies, demonstrated closer alignment with the official HICP while capturing more detailed price fluctuations within the market. Monthly inflation trends revealed variability that reflects price changes in the COICOP 091 category, contrasting with the relative stability of the official HICP. This work provides an alternative perspective on inflation measurement, highlighting the potential of computational approaches to enhance economic analysis.